2009
DOI: 10.3928/01913913-20090903-07
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pathologic Study of a Cohort of Patients With Retinoblastoma From a Developing Country

Abstract: In this study, the percentage of patients with choroidal and optic nerve invasion, reflecting a poor prognosis, was much higher than in previously reported North American series. However, similar findings have been described in other developing countries, where late diagnosis is common. This study emphasized the need for early diagnosis and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
13
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 18 publications
4
13
1
Order By: Relevance
“…The overall reported incidence of optic nerve involvement beyond the lamina cribrosa and at the resection margin ranged from 6.5% to 40%, while the overall reported incidence of massive choroid invasion ranged from 12% to 41%. In our series, 18% of eyes had massive choroid invasion and 14% had post laminar optic nerve invasion, which is comparable to the results reported from the developed world, and is less than the results reported from the developing world (Table V) (10,11,15,18,19,24,(28)(29)(30). The higher incidence of these risk factor in developing world might be related to later presentation (more advanced stage) in relation to the lower socioeconomic status and the delay in getting the needed treatment.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…The overall reported incidence of optic nerve involvement beyond the lamina cribrosa and at the resection margin ranged from 6.5% to 40%, while the overall reported incidence of massive choroid invasion ranged from 12% to 41%. In our series, 18% of eyes had massive choroid invasion and 14% had post laminar optic nerve invasion, which is comparable to the results reported from the developed world, and is less than the results reported from the developing world (Table V) (10,11,15,18,19,24,(28)(29)(30). The higher incidence of these risk factor in developing world might be related to later presentation (more advanced stage) in relation to the lower socioeconomic status and the delay in getting the needed treatment.…”
Section: Discussionsupporting
confidence: 57%
“…Most of these reported higher incidences compared with studies reported from the developed world (15)(16)(17)(18)(19)(20)(21).…”
Section: Introductioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Previously published studies from developing countries have shown a higher incidence of histopathological high risk factors (HRF) in eyes enucleated for retinoblastoma [7,8]. Some clinical features have shown to be associated with the presence of high risk factors [3,4,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] This has been attributed to delay in presentation and diagnosis, lack of specialized centers, and/or differences in biologic behavior of the tumors.…”
mentioning
confidence: 99%